PENGARUH MOTIVASI BELAJAR SISWA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN KEWIRAUSAHAAN DI SMK MUHAMMADIYAH 1 PEKANBARU - Wijayanti, Niken; Johan, Rina Selva; ', Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research came up because of the students’ decreased achievement of class X and X1 in the entrepreneurship subject of the first semester in the academic year of 2015/2016.183 out of 645 students gained under minimum passing grade (KKM) in the entrepreneur subject. This phenomenon happened because of some factors. One of them was an unmotivated learning indicated by the laziness to engage the teaching learning process, such as the frequent going in and out of the class, absence, and not doing the task given by the teacher. This research aimed at investigating in what extent the influence of students’ learning motivation towards the learning achievement of the students having under minimum passing grade at the entrepreneurship subject at SMK Muhammadiyah 1 Pekanbaru. The population of this research was 183 students with 65 students as the samples. Probability sampling, simple random sampling, is used as the technique to gain the sample in this research. The data were collected using observation, questionnaire, and documentation. Based on the data analysis, it can be concluded that the significance value in the coefficient table 0.000 is less than critical value 0.1. Thus, it is obtained that 0.000 < 0.1, which means that the students’ learning motivation influences the students’ learning achievement in the entrepreneurship subject at SMK Muhammadiyah 1 Pekanbaru. Viewed from the R square 0.207 shows that the independent variable student learning motivation used in this research is influenced by the dependent variable student learning achievement at the rate of 20.7%. Thus, it can be said that the capability of the independent variable student learning motivation in influencing the dependent variable student learning achievement is high. Based on the calculation of t test, the t table 4,057 > t quantification 1.998 (Ho) is rejected or sig 0.000 < 0.05 (Ha) is accepted. It means that there is an influence of the students’ learning motivation towards the students’ learning achievement. Based on the regression coefficient, if the students’ learning motivation happens to increase at rate of 1%, the students’ learning achievement also will increase at the rate of 0.284 or 28.4%. The positive coefficient shows that there is positive correlation between students’ learning achievement and students’ learning motivation. The more students are motivated, the more students will reach the achievement.Keywords: Students’ Learning Motivation, Students’ Learning Achievement2